2019
DOI: 10.3390/ani9070409
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Equine-Assisted Therapy on Equine Behavioral and Physiological Responses

Abstract: Equine-assisted therapies (EATs) have been widely used in the treatment of patients with mental or physical conditions. However, studies on the influence of equine-assisted therapy (EAT) on equine welfare are very recent, and the need for further research is often highlighted. The aim of this study was to investigate whether EAT creates negative or positive emotions in horses, and the influence of patients’ expectations (one group of patients had physical and psychological expectations and one group of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
1
20
0
2
Order By: Relevance
“…In our study, the horse HR was lower than 75 beats per min while riding (at the walk), and the avoidance and agonistic behaviours observed were low intensity (e.g., ears back, tossing head, swishing tail, reluctance to obey rider’s command). Therefore, our results do not suggest that therapy horses in this EFL program showed signs of physiological or behavioural distress, in line with previous research [ 3 , 20 , 27 , 31 , 32 ]. Therapy horses in our study certainly showed affiliative behaviours toward adolescents during grooming and the first riding sessions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the horse HR was lower than 75 beats per min while riding (at the walk), and the avoidance and agonistic behaviours observed were low intensity (e.g., ears back, tossing head, swishing tail, reluctance to obey rider’s command). Therefore, our results do not suggest that therapy horses in this EFL program showed signs of physiological or behavioural distress, in line with previous research [ 3 , 20 , 27 , 31 , 32 ]. Therapy horses in our study certainly showed affiliative behaviours toward adolescents during grooming and the first riding sessions.…”
Section: Discussionsupporting
confidence: 89%
“…These results indicate that therapy horses were sensitive to behavioural and/or emotional differences associated with the human AS of adolescents participating in an EFL program. Previous results indicated that the physiological and behavioural response of horses can be affected by human traits [ 9 , 10 , 26 , 27 ]. Merkies and colleagues [ 9 ] reported that horses had a lower HR when in the presence of humans that ranked themselves as fearful around horses.…”
Section: Discussionmentioning
confidence: 99%
“…Both physiological and behavioural measures of horse response to human interactions were reported in 42.2% (n = 19) of studies; a further 31.1% (n = 14) exclusively used physiological measures and 26.6% (n = 12) used qualitative measures (i.e., behavioural observation). Only six papers described studies that included a control group or condition [38][39][40][41][42][43].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Approximately three quarters of the studies in the present review used physiological measurements to explore the effect of the HHIs. Heart rate (HR) data was obtained in 27 studies [37][38][39][40][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Of these studies, 23 used the Polar HR monitor on horses alone, while 2 studies used the Polar HR monitor on horses and humans [38,45].…”
Section: Physiological Measuresmentioning
confidence: 99%
“…Ansiedade-Estado Antes (nq=20) 55.0 (11) 5.0 (1) 20.0 (4) 20.0 (4) Depois (nq=20) 75.0 (15) 25.0 (5) 0.0 (0) 0.0 (0) Os benefícios psicológicos, comportamentais e motores frente à prática de equoterapia são amplamente descritos na literatura (MARTÍN-VALERO et al, 2018;PEPPE et al, 2018;ROMANIUK et al, 2018;MENDONÇA et al, 2019). Entretanto, são escassos os estudos avaliando, simultaneamente, o efeito desta TAA sobre a ansiedade e a qualidade de vida, principalmente quando se trata de idosos institucionalizados.…”
Section: (Muitíssimo)unclassified